(3eTGcd GdeYGedGJ GdeGdjI Hjf GdTQY hGdYQas - (3MSGf eMehO(B, (3YHO Gddgs ((3HjQhJ(B:s (3OGQ GdgGOj ddWHGYI hGdfTQ(B,s, 2008)
(3eTGcd GdeYGedGJ GdeGdjI,GdJLGQI BOGHgG heTGcdgG,GdecGSH GdeMQeI,GdHjY heTGcdg,GdELGQI,GdYed hMbhb GdYGed,GdCLQI Ydi GdhGLHGJ,GdOdGdI hGdSeSQI,GdGSJKeGQGJ GdeGdjI,GdeYGedGJ GdQHhjI,GdeRGQYI,GdQgf,GdMLQ,GdMhGdI,GdTQcI,GdeTJQcGJ,GdJCejfs
(3HHdjhZQGajG(B:(3U U(B.561-564s
Keywords: (3GdeGdjIs; (3GdeYGedGJ(B-(3abg GSdGejs